Association Between Blood Pressure Variability and Cerebral Small‐Vessel Disease: A Systematic Review and Meta‐Analysis - Tully, Phillip J. (J Am Heart Assoc, 2019)
BACKGROUND: Research links blood pressure variability (BPV) with stroke; however, the association with cerebral small‐vessel disease (CSVD) remains unclear. As BPV and mean blood pressure are interrelated, it remains uncertain whether BPV adds additional information to understanding cerebrovascular morphological characteristics. METHODS AND RESULTS: A systematic review was performed from inception until March 3, 2019. Eligibility criteria included population, adults without stroke (<4 weeks); exposure, BPV quantified by any metric over any duration; comparison, (1) low versus high or mean BPV and (2) people with versus without CSVD; and outcomes, (1) CSVD as subcortical infarct, lacunae, white matter hyperintensities, cerebral microbleeds, or enlarged perivascular spaces; and (2) standardized mean difference in BPV. A total of 27 articles were meta‐analyzed, comprising 12 309 unique brain scans. A total of 31 odds ratios (ORs) were pooled, indicating that higher systolic BPV was associated with higher odds for CSVD (OR, 1.27; 95% CI, 1.14–1.42; I(2)=85%) independent of mean systolic pressure. Likewise, higher diastolic BPV was associated with higher odds for CSVD (OR, 1.30; 95% CI, 1.14–1.48; I(2)=53%) independent of mean diastolic pressure. There was no evidence of a pairwise interaction between systolic/diastolic and BPV/mean ORs (P=0.47), nor a difference between BPV versus mean pressure ORs (P=0.58). Fifty‐four standardized mean differences were pooled and provided similar results for pairwise interaction (P=0.38) and difference between standardized mean differences (P=0.70). CONCLUSIONS: On the basis of the available studies, BPV was associated with CSVD independent of mean blood pressure. However, more high‐quality longitudinal data are required to elucidate whether BPV contributes unique variance to CSVD morphological characteristics.